Treatment of dysarthria following subthalamic nucleus deep brain stimulation for Parkinson’s disease - Tripoliti, Elina (2011)
Deep brain stimulation of the subthalamic nucleus (STN-DBS) is an established treatment for patients with Parkinson’s disease (PD). Speech impairment is a frequent side effect of the surgery. This study examined the efficacy of an intensive speech treatment (the Lee Silverman Voice Treatment, LSVT) on dysarthria after STN-DBS. The LSVT was administered in ten patients with STN-DBS (surgical group) and ten patients without (medical group). Patients were assessed before, immediately after and six months following the speech treatment using sustained phonation, a speech intelligibility scale and monologue. Vocal loudness, speech intelligibility and perceptual ratings were the primary outcome measures. Vocal loudness and perceptual scores improved significantly across tasks for the medical group only. Speech intelligibility did not significantly change for either group. Results in the surgical group were variable with some patients deteriorating. Treatment of dysarthria following STN-DBS needs further investigation due to the variable response to LSVT.